2011
DOI: 10.1021/ef2003443
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Coal-Derived and Petroleum Asphaltenes by 13C Nuclear Magnetic Resonance, DEPT, and XRS

Abstract: The molecular architecture of asphaltenes is still a matter of debate. Some literature reports provide evidence that the contrast of petroleum asphaltenes versus coal-derived asphaltenes is useful for understanding the governing principles of asphaltene identity. Coal-derived asphaltenes provide an excellent test for understanding the relationship of asphaltene molecular architecture with asphaltene properties. Diffusion measurements have shown that coal-derived asphaltenes are half the size of many crude oil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

34
197
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 109 publications
(234 citation statements)
references
References 64 publications
34
197
3
Order By: Relevance
“…yielding ∼7 PAHs in virgin petroleum asphaltenes, with ∼6 PAHs in coal-derived asphaltenes. 59 This NMR study provided direct interrogation of aromatic carbon bonded to hydrogen as opposed to assigning a spectra cutoff. The corresponding method is distortionless enhancement by polarization transfer (DEPT) NMR.…”
Section: Energy and Fuelsmentioning
confidence: 99%
See 2 more Smart Citations
“…yielding ∼7 PAHs in virgin petroleum asphaltenes, with ∼6 PAHs in coal-derived asphaltenes. 59 This NMR study provided direct interrogation of aromatic carbon bonded to hydrogen as opposed to assigning a spectra cutoff. The corresponding method is distortionless enhancement by polarization transfer (DEPT) NMR.…”
Section: Energy and Fuelsmentioning
confidence: 99%
“…Thus, coal-derived asphaltenes are much lower in molecular weight and also have smaller PAHs than petroleum asphaltenes. 29,50,59 Petroleum resid asphaltene with its reduced alkane content also exhibits reduced PAH size. 63 Initial asphaltene molecules that are subject to alkane removal by cracking in distillation become less soluble forming coke.…”
Section: Energy and Fuelsmentioning
confidence: 99%
See 1 more Smart Citation
“…They comprise 63 the fraction of petroleum that is soluble in toluene but insoluble 64 in n-alkane [4] and can correspond to up to 20% of crude oil [5]. 65 The elucidation of the structures of the molecules in asphaltenes 66 has far reaching implications [3] since asphaltenes clog pipes used 67 for transportation of crude oil and poison catalysts used in refining 68 [1,[6][7][8][9][10][11]. Further, only few uses exist for asphaltenes, including 69 expensive upgrading to distillates [12], road construction [13] 70 and recently proposed use in organic electronic materials [14,15] [9] to be especially well suited for evaporation and ionization of 114 asphaltenes since it has no bias to more polar analytes and it pro-115 duces only one ion type, molecular ion (M +Å ), for all asphaltene 116 model compounds studied [9].…”
mentioning
confidence: 99%
“…In conceptually simple, robust, surfacetension studies, the PAH (polycyclic aromatic hydrocarbon) size for several asphaltene types has been confirmed [33,34]. NMR studies have also confirmed the asphaltene PAH sizes, [35,36] given the asphaltene orientation at the interface [37]. Alicyclic rings fused to aromatic rings have been confirmed by heteronuclear single quantum coherence NMR studies [36].…”
Section: Introductionmentioning
confidence: 81%